Reviews of educational toys designs in cultivating social competence of pre school children - Loy, Jia Shin; Abdul Rahman, Ahmad Rizal (Universiti Putra Malaysia, 2019)
There is a need to embed social development attributes in educational toys design to cultivate children acquire higher competency personalities. The purpose of this paper is to analyse the attributes of social development through educational toys design in cultivating social and emotional development among preschool children. This study uses Literature Review to analyse the attributes of social skills development for educational toys designs. Prior investigation is carried out on methods in promoting positive social development towards young children and to understand the influence of educational toys design on children's play environment. Additionally, this paper also uses Literature Review to document social behavioural aspects of preschool children in Malaysia. The results are expected to lead towards the theoretical framework or guidelines in designing educational toys for the social development of children. This review will serve as a decree for consumers and product manufacturers to have a deeper understanding towards the social and emotional development of children, which would nurture the growth of their moral compass and improve their attitudes. Lastly, this paper is expected to contribute to the sustainable development in human ecology.